2022
DOI: 10.1158/0008-5472.can-21-2105
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Ancestry and Molecular Signatures with Cancer Survival Disparities: A Pan-Cancer Analysis

Abstract: While overall cancer mortality has steadily decreased in recent decades, cancer health disparities among racial and ethnic population groups persist. Here we studied the relationship between cancer survival disparities (CSD), genetic ancestry (GA), and tumor molecular signatures across 33 cancers in a cohort of 9,818 patients. GA correlated with race and ethnicity but showed observable differences in effects on CSD, with significant associations identified in four cancer types: breast invasive carcinoma (BRCA)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…The expression level of CCNF in male patients is generally higher than that in female patients, which also suggests that CCNF is a potential pancancer therapeutic target influenced by sex. There are similar differences in patients grouped by race ( 45 , 46 ). In our study, the expression level of CCNF in Caucasians with BLCA and THYM cancer was significantly lower than that in African Americans but significantly higher than that in Asians.…”
Section: Discussionmentioning
confidence: 77%
“…The expression level of CCNF in male patients is generally higher than that in female patients, which also suggests that CCNF is a potential pancancer therapeutic target influenced by sex. There are similar differences in patients grouped by race ( 45 , 46 ). In our study, the expression level of CCNF in Caucasians with BLCA and THYM cancer was significantly lower than that in African Americans but significantly higher than that in Asians.…”
Section: Discussionmentioning
confidence: 77%
“…In order to better explore the genomic profiles between the 3 clusters, we adopted the tumor molecular signatures across 33 cancers from the TCGA cohort ( 14 ), and identified that C1 had a remarkably higher aneuploidy score ( Figure 3A ), homologous recombination defects ( Figure 3B ), fraction altered ( Figure 3C ), and number of segments ( Figure 3D ), as compared with C3. The tumor mutation burden was higher in C3 than C2 ( Figure 3E ).…”
Section: Resultsmentioning
confidence: 99%
“…MXD3, a member of the MXD family, plays pivotal roles in cell cycle progression and cell proliferation; it is regarded as an onco- Frontiers in Genetics frontiersin.org immunological biomarker (Wu et al, 2021). Moreover, pan-cancer analysis discovered that MXD3 interacted with gene ancestry (GA) and exacerbated observed survival disparities (Lee et al, 2022). Besides, MXD3 was reported to be a potential therapeutic target in pre-B cell acute lymphoblastic leukemia (Satake et al, 2014).…”
Section: Discussionmentioning
confidence: 99%